The Development of Intimacy Feelings and its Relationship with Altruistic Behavior among University Students - Ahmed, Chachan J.; Qader, Evan A. (Humanities Journal of University of Zakho, 2015)
The study aimed to identify the level of development of intimacy feelings and altruistic behavior among the university students, the disclosure of the significance of the differences in each variable according to the gender and academic specialization, as well as detecting the nature of the relationship between the variables of intimacy and altruistic behavior. The sample consisted of (345) students who were selected from six colleges in Salahaddin University in Erbil. The study relied on the application of two tools: the first is the intimacy scale which consists of 40 items, in front of each item there are four alternatives for the answer. And the second application is the measure of altruistic behavior which consists of (24) hypotheses situation with three choices for the answer. The statistical data were analyzed by using Pearson’s correlation coefficient, and Spearman& Brown’s correction equation, as well as the t-test for one sample and two independent samples. The results revealed that the level of the intimacy feeling and the altruistic behavior is high among the students of the university, and found significant differences attributable to the variables of gender and academic specialization in the feeling of intimacy and altruistic behavior in favor of males, as well as in favor of human specialization. The results also indicate a positive relationship between the variables of intimacy and altruistic behavior. In the light of the results recommendations have been presented.